Size and scale economies in the Israeli industry: Effects of the Free Trade Area agreement with the Common Market - Benjamin Toren (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1977)
In May 1975 an agreement was concluded on the gradual establishment of a Free Trade Area between Israel and the Common Market. This agreement improved the access of Israeli exports to the European market between 1975 and 1977 and gave Israeli exporters an important new potential to step up their export sales to the Common Market. On the other hand, the agreement will improve the access of European exporters to the Israeli market in a gradual transition period up to 1985 or possibly 1989 and thus will increase competition for the Israeli industry, which enjoyed relatively high protection in the past, This new situation offers many possible gains but involves also great risks. It will only contribute to industrial development if the competitiveness of Israeli producers both in the domestic as well as the export market is substantially increased. A number of factors can be considered as a potential means of achieving the needed level of competitiveness. These may include static trade effects connected directly with the rise in prices of, or the rise in demand for exports and the fall in prices or rise in supply of imports and import substitutes; an increase in productivity in existing plants, often referred to as X-efficiency, through higher specialization, better quality, better utilization of existing capacity, better utilization of existing capacity, better work morale, etc.; - an improvement in technology; a shiftover from less competitive to more competitive products and industries; an increase in capital investments; with or without foreign participation; this factor is always connected with the next; an increase in the size of plants and scale economies, which is defined to exist when all factors of production are increased by the same proportion.
Keywords: 330